Investigating shared risk variants and genetic etiology between Alzheimer’s disease and three stress-related psychiatric disorders: a large-scale genome-wide cross-trait analysis - Dang, Weijia; Hao, Tianqi; Li, Ning; Zhang, Hualin; Li, Ziqi; Yu, Hongmei; Wen, Yalu; Zheng, Deqiang; Liu, Long (Frontiers in Aging, 2025)
IntroductionObservational studies have reported that patients with Alzheimer’s disease (AD) have a greater burden of comorbidities typically associated with stress-related psychiatric disorders. However, the contribution of hereditary factors to this comorbidity remains unclear. We evaluated phenotypic associations using observational data from the UK Biobank.MethodOur study focused on investigating the shared risk variants and genetic etiology underlying AD and three stress-related psychiatric disorders: post-traumatic stress disorder, anxiety disorder, and major depressive disorder. By leveraging summary statistics from genome-wide association studies, we investigated global genetic correlations using linkage disequilibrium score regression, genetic covariance analysis, and high-definition likelihood. Genome-wide cross-trait analysis with association analysis based on subsets and cross-phenotype association were performed to discover genome-wide significant risk variants shared between AD and the three stress-related psychiatric disorders.ResultsA significant positive genetic correlation was observed between AD and major depressive disorder using linkage disequilibrium score regression (rg = 0.231; P = 0.018), genetic covariance analysis (rg = 0.138; P < 0.001), and high-definition likelihood (rg = 0.188; P < 0.001). Association analysis based on subsets and cross-phenotype association revealed thirteen risk variants in six genes shared between AD and post-traumatic stress disorder; seven risk variants in four genes shared between AD and anxiety disorder; and 23 risk variants in four genes shared between AD and major depressive disorder. Functional annotation and gene-set enrichment analysis indicated that 12 genes for comorbidity shared between patients with AD and all three stress-related psychiatric disorders were enriched in the spleen, pancreas, and whole blood.ConclusionThese results advance our knowledge of the shared genetic origins of comorbidities and pave the way for advancements in the diagnosis, management, and prevention of stress-related AD.